Long-term unemployment and work deprived individuals: issues and policies - Dockery, Alfred Michael; Webster, E. (The Centre for Labour Market Research, 2002)
The incidence of very long term unemployment has risen by nearly 1 per cent per annum since the late 1970's. Australian labour market programs were not specially targeted to the very long-term unemployed until the introduction of the Job Compact in 1994. Despite concerted active measures taken since then, along with highly favourable growth conditions, there remain nearly 100 000 people in Australia who have been unemployed for over two years. The majority of these people have been workless for a large portion of their working lives.There is a broad consensus that the net impact effects of programs for the work deprived are either small or very small. For all that has been tried, sadly we have not learnt a great deal as to what programs work for different people and why. We argue that this is due in part to deficiencies in past and ongoing evaluation efforts, including the lack of rigorous research designs and access to data for independent researchers. Second, labour market programs are regarded by evaluations as a 'black box' into which the unemployed enter and come out at the other end either employed or not, with little attention paid to the nature of the barriers faced by the work deprived and the appropriate treatments. An initial analysis identifies five different clusters of work deprived individuals. Policy suggestions include more targeted assistance for these clusters and enduring job creation programs, combined with an enhanced evaluation effort to guide future policy.